Study on the biological effects of ZnO nanosheets on EBL cells - Li, Mei; Ma, Yonghua; Lian, Xiaodi; Lu, Yan; Li, Yuanyuan; Xi, Yao; Sun, Xiaolin (Frontiers in Bioengineering and Biotechnology, 2022)
In this study, the biological effects of ZnO nanosheets were initially investigated using embryonic bovine lung (EBL) cells cultured in vitro as a model. ZnO nanosheets were prepared by a hydrothermal method, and their structure and morphology were characterized, and their effects on EBL cell viability, oxidative stress, cell proliferation, and apoptosis were investigated. The results showed that 12.5 μg ml−1 ZnO nanosheets can cause morphological changes in EBL cells. The toxic effects of ZnO nanosheets on EBL cells were time-dependent. Caspase-3 activity in EBL cells changed under certain conditions with the introduction of 25 μg ml−1 ZnO nanomaterials, and EBL cell apoptosis was promoted. Under different concentration and time effects, ZnO nanosheets induced an increase in ROS levels in EBL cells, indicating that they have an oxidative damage effect on cells. The toxic effects of ZnO nanosheets on EBL cells were discussed, including concentration effect, time effect, and cytotoxic effect, which eventually led to cell oxidative damage.